Notalgia Paresthetica - Mirna Šitum (Acta Clinica Croatica, 2018)
Notalgia paresthetica is a common, although under-recognized condition characterized by localized chronic pruritus in the upper back, most often affecting middle-aged women. Apart from pruritus, patients may present with a burning or cold sensation, tingling, surface numbness, tenderness and foreign body sensation. Additionally, patients often present with hyperpigmented skin at the site of symptoms. The etiology of this condition is still poorly understood, although a number of hypotheses have been described. It is widely accepted that notalgia paresthetica is a sensory neuropathy caused by alteration and damage to posterior rami of thoracic spinal nerves T2 through T6. To date, no well-defined treatment has been found, although many treatment modalities have been reported with varying success, usually providing only temporary relief.